How can higher education enhance social adaptation and minimize struggles among international students? - Jiewei, Wu; Kurniady, Dedy Achmad; Komariah, Aan; Sururi; Nugraha, Rizki Satria; Ruhimat, Mochammad Devi Cahya; Shuhua, Zhang (Journal of International Students, 2026)
As international student mobility grows, persistent adaptation challenges expose a gap between internationalization discourse and institutional practice in Indonesian higher education, highlighting the lack of an evidence-based, context-sensitive framework to effectively support international students. This study introduces the International Student Academic Management (ISAM) model, a framework designed to enhance institutional interventions for international students’ social adaptation and to mitigate their adjustment challenges. Employing Straussian Grounded Theory (SGT) with a qualitative approach, this study addresses persistent integration issues, particularly among Chinese students in Indonesian higher education institutions. Data were generated from 24 participants, including international students, academic staff, international office administrators, and deans, through semi-structured interviews, document analysis, and reflexive fieldwork. The ISAM comprises four interrelated dimensions: Transitional Anchoring, Academic Mediation, Institutional Reflexivity and Adaptation, and Participatory Governance and Strategic Alignment. These dimensions collectively respond to critical gaps in institutional practice and theorization.